2011
DOI: 10.1111/j.1464-410x.2011.10374.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment changes and long‐term recurrence rates after hexaminolevulinate (HAL) fluorescence cystoscopy: does it really make a difference in patients with non‐muscle‐invasive bladder cancer (NMIBC)?

Abstract: 4 9What ' s known on the subject? and What does the study add? HAL fl uorescence cystoscopy is known to improve tumour detection in NMIBC cases and to have a potentially favourable impact concerning the recurrence rates.The present trial assessed the advantages of HAL cystoscopy with regard to postoperative treatment changes and 2 years ' recurrence rates, subjects that are poorly evaluated in the literature. OBJECTIVES• To evaluate in a prospective, randomized study the impact of hexaminolevulinate blue-light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 30 publications
1
69
1
5
Order By: Relevance
“…At 2 years of follow up the rates were 4% versus 7% (p = 0.123) [Geavlete et al 2012]. Similarly, Grossmann and colleagues found a trend towards improvement of tumor-free survival and bladder preservation.…”
Section: Progression To Muscle-invasive Bladder Carcinomamentioning
confidence: 84%
See 2 more Smart Citations
“…At 2 years of follow up the rates were 4% versus 7% (p = 0.123) [Geavlete et al 2012]. Similarly, Grossmann and colleagues found a trend towards improvement of tumor-free survival and bladder preservation.…”
Section: Progression To Muscle-invasive Bladder Carcinomamentioning
confidence: 84%
“…No phototoxicity is observed and most adverse events are mild and seem to be related to the tumor and the resection rather than to the photosensitizing drug [Hermann et al 2011;Geavlete et al 2012;Lapini et al 2012]. Frequently mentioned adverse events are bladder pain, bladder spasm, dysuria and hematuria.…”
Section: Safety and Costsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensitivity and specificity of WLC and PDD are 46%-80% and 76-97%, and 43%-98% and 35-66%, respectively. (Zaak and Hofstetter, 2002;Grimbergen et al, 2003;Jichlinski et al, 2003;Schmidbauer et al, 2004;Fradet et al, 2007;Grossman et al, 2007;Jocham et al, 2008;Stenzl et al, 2008;Geavlete et al, 2012) Now PDD is emerging to diagnose NMIBC or carcinoma in situ. However no studies specifically used PDD for muscle invasive bladder cancer, cystoscopic observation for BCG failure cases or 2nd-TUR cases.…”
Section: Introductionmentioning
confidence: 99%
“…Six studies reported additional Ta tumor detection rates with BLC, ranging from 9% to 42% of the total Ta tumors detected [Jocham et al 2005;Schmidbauer et al 2004;Grossman et al 2007;Burguèsa et al 2011;Geavlete et al 2011;Lapini et al 2012], with a proportion difference of 5.9% (95% CI 0.014-0.103) of additional lesion detection rates with BLC. The same studies reported additional T1 tumor detection rates ranging from 4.9% to 9% of the total T1 tumors detected [Schmidbauer et al 2004;Fradet et al 2007;Burguèsa et al 2011;Geavlete et al 2011;Lapini et al 2012], only Jocham and colleagues showed no differences in T1 tumors detection rates [Jocham et al 2005].…”
Section: Lesion Detection Ratementioning
confidence: 99%